The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1021/am5050949
|View full text |Cite
|
Sign up to set email alerts
|

Directed Assembly of Bifunctional Silica–Iron Oxide Nanocomposite with Open Shell Structure

Abstract: The synthesis of nanocomposite with controlled surface morphology plays a key role for pollutant removal from aqueous environments. The influence of the molecular size of the polyelectrolyte in synthesizing silica-iron oxide core-shell nanocomposite with open shell structure was investigated by using dynamic light scattering, atomic force microscopy, and quartz crystal microbalance with dissipation (QCM-D). Here, poly(diallydimethylammonium chloride) (PDDA) was used to promote the attachment of iron oxide nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 69 publications
0
22
0
Order By: Relevance
“…The slope of ΔD to Δf was steepest with Al o , followed by Al 30 and Al 13 , which indicated that the deposited layer of Al 13 was the most rigid and a most soft dissipative film was formed for Al o . For Al 13 and Al 30 , with direct inspection, the slope of ΔD to Δf exhibited a linear relationship, which meant that no conformational alternation occurred during the deposition process (Che et al, 2014). With respect to Al o , the slope became larger with increasing | Δf | , which meant that the film became more loosely attached to the surface (Li et al, 2014).…”
Section: Deposited Layer Characteristicsmentioning
confidence: 97%
“…The slope of ΔD to Δf was steepest with Al o , followed by Al 30 and Al 13 , which indicated that the deposited layer of Al 13 was the most rigid and a most soft dissipative film was formed for Al o . For Al 13 and Al 30 , with direct inspection, the slope of ΔD to Δf exhibited a linear relationship, which meant that no conformational alternation occurred during the deposition process (Che et al, 2014). With respect to Al o , the slope became larger with increasing | Δf | , which meant that the film became more loosely attached to the surface (Li et al, 2014).…”
Section: Deposited Layer Characteristicsmentioning
confidence: 97%
“…[50] On the other hand, amoxicillin molecules were detected to have a zeta potential level showing small positive charges. [51] We postulate that Mn0.3Fe2.7O4@SiO2 NPs and amoxicillin can be coupled directly by electrostatic interactions to form amoxicillin loaded Mn0.3Fe2.7O4@SiO2. The zeta potential was measured to confirm the coupling.…”
Section: Figurementioning
confidence: 95%
“…As a result, chemical synthesis methods are exploited to synthesize FeONPs. The common ways to synthesize FeONPs chemically are co-precipitation [11], sol-gel method [12], microemulsion [13], thermal decomposition [14], and sonochemical synthesis [15]. Inevitably, there are also some drawbacks on it which are the adoption of toxic reducing agents such as sodium borohydride and hydrazine hydrate [16], and pollution caused by the iron precursor chemicals [10].…”
Section: Introductionmentioning
confidence: 99%